2016
DOI: 10.3892/ol.2016.4381
|View full text |Cite
|
Sign up to set email alerts
|

Derived neutrophil/lymphocyte ratio predicts gemcitabine therapy outcome in unresectable pancreatic cancer

Abstract: Abstract.As gemcitabine is a key anti-tumor agent for unresectable pancreatic ductal adenocarcinoma (PDAC), it is important to predict the outcomes of gemcitabine chemotherapy. The present study aimed to confirm whether the derived neutrophil-to-lymphocyte ratio (dNLR) is able to predict chemotherapy outcomes. To elucidate the role of dNLR in patients that underwent chemotherapy, the current study evaluated clinicopathological variables in 31 patients with unresectable PDAC treated with gemcitabine. The correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 23 publications
0
31
0
Order By: Relevance
“…In patients with resectable PDAC, preoperative NLR (15), PLR (16,17), GPS (18) and PNI 45 (7) were reported to be factors in early recurrence and poor prognosis after surgical resection. In unresectable PDAC, previous reports showed that patients with a high NLR had a shorter OS time (13,19). In terms of GPS, a retrospective study Table III.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In patients with resectable PDAC, preoperative NLR (15), PLR (16,17), GPS (18) and PNI 45 (7) were reported to be factors in early recurrence and poor prognosis after surgical resection. In unresectable PDAC, previous reports showed that patients with a high NLR had a shorter OS time (13,19). In terms of GPS, a retrospective study Table III.…”
Section: Discussionmentioning
confidence: 96%
“…1. We previously reported that NLR is useful for predicting the outcome of gemcitabine therapy in unresectable PDAC (13). However,…”
Section: Introductionmentioning
confidence: 97%
“…26,27 These might partially explain why an elevated NLR is associated with poor survival. Recent clinical studies revealed that dNLR was associated with chemotherapy response 10,28 and prognosis in many advanced cancers, such as metastatic melanoma, 8 metastatic castration-resistant prostate cancer, 9 advanced biliary cancer, 10 and advanced colorectal cancer. 29 The dNLR is composed of WBCs and neutrophils; this parameter has been proposed as an alternative to NLR for studies where only WBCs and neutrophils have been recorded.…”
Section: Discussionmentioning
confidence: 99%
“…The PRISMA flow chart of the systematic review can be found in Figure . An initial search done using the search strategy (Supporting Materials) obtained an initial 900 results.…”
Section: Methodsmentioning
confidence: 99%